Penitentiary integral defense - Rodríguez Román, Francisco Javier (Revista de Artes Marciales Asiáticas, 2012)
Penitentiary integral defense is a set of techniques designed to solve the breach of the peace that may appear in the penitentiary world. This paper studies the scope and legal framework of penitentiary self-defense. This kind of self-defense is defined by the particular characteristics of a confinement context and a very specific regulation aimed at preserving the integrity of prisoners and penitentiary staff as well as prison facilities. A technical section illustrating the main penitentiary integral defense’s fundamentals and methods is also included. The defense methods showed here are: frisking, confinement cell entry, prisoner transfer, active resistance, aggressions between prisoners, standard defense equipment, handcuffs use, and techniques against holds, non-armed attacks and attacks with an edged weapon.